High-Speed Privacy Amplification Scheme Using GMP in Quantum Key Distribution - Bingze Yan; Qiong Li; Haokun Mao; Xiaofeng Xue (IEEE Photonics Journal, 2020)
Privacy amplification (PA) is the art of distilling a highly secret key from a partially secure string by public discussion. It is a vital procedure in quantum key distribution (QKD) to produce a theoretically unconditional secure key. The throughput of PA has become the bottleneck of most high-speed discrete variable QKD (DV-QKD) systems. Although some Toeplitz-hash PA schemes can meet the demand of throughput, their high throughput extremely depends on the high cost platform, such as MIC or GPU. From the comprehensive view of development cost, integration level and power consumption, CPU is a general low cost platform. However, the throughput of CPU based PA scheme is not satisfactory so far, mainly due to the conflict between the intrinsic serial characteristic of CPU and the parallel requirement of high throughput Toeplitz-hash PA scheme. In this paper, a high throughput modular arithmetic hash PA scheme using GNU multiple precision arithmetic library (GMP) based on CPU platform is proposed. The experimental results show that the throughput of our scheme is nearly an order of magnitude higher than the comparative scheme on the similar CPU platform, which is 135 Mbps and 69 Mbps at the block sizes of $10^6$ and $10^8$ on Intel i3-2120 CPU respectively. Moreover, our scheme can provide the best throughput among DV-QKD PA schemes, which is 260 Mbps and 140 Mbps at the block sizes of $10^6$ and $10^8$ on Intel i9-9900k CPU respectively.